2005
DOI: 10.1016/s0002-9440(10)62959-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling of Giant Cell Tumor of Bone and the Osteoclastic Localization of Ligand for Receptor Activator of Nuclear Factor κB

Abstract: Giant cell tumor of bone (GCT) is a generally benign, osteolytic neoplasm comprising stromal cells and osteoclast-like giant cells. The osteoclastic cells, which cause bony destruction, are thought to be recruited from normal monocytic pre-osteoclasts by stromal cell expression of the ligand for receptor activator of nuclear factor kappaB (RANKL). This model forms the foundation for clinical trials in GCTs of novel cancer therapeutics targeting RANKL. Using expression profiling, we identified both osteoblast a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 55 publications
1
87
0
3
Order By: Relevance
“…17,18 Interestingly, TP73L whose protein product is p63 was among the significantly upregulated genes identified for GCTOB even though none of the earlier gene expression profiling studies on GCTOB identified p63 as being highly expressed. 15,16,19 A closer examination of the TP73L expression in this series of tumors revealed that its expression was the highest in four of the six GCTOB whereas the other two GCTOB showed similar levels of TP73L expression as seen in ABC and FD. GCTTS/DTGCT showed a much lower level of TP73L in contrast to GCTOB.…”
Section: Gene Expression Profiling Studymentioning
confidence: 59%
See 2 more Smart Citations
“…17,18 Interestingly, TP73L whose protein product is p63 was among the significantly upregulated genes identified for GCTOB even though none of the earlier gene expression profiling studies on GCTOB identified p63 as being highly expressed. 15,16,19 A closer examination of the TP73L expression in this series of tumors revealed that its expression was the highest in four of the six GCTOB whereas the other two GCTOB showed similar levels of TP73L expression as seen in ABC and FD. GCTTS/DTGCT showed a much lower level of TP73L in contrast to GCTOB.…”
Section: Gene Expression Profiling Studymentioning
confidence: 59%
“…15,16,19 Thomas and co-workers have recently published the gene expression profile of 9 GCTOB together with a series of undifferentiated pleomorphic sarcomas, liposarcomas, leiomyosarcomas and synovial sarcomas for comparison. 15 Although they found relatively high expression of TP73L in 3 of the 9 GCTOB, they also noted expression in 3 of 11 undifferentiated pleomorphic sarcomas, 3 of 9 leiomyosarcomas and 1 of 4 synovial sarcomas with similarly high expression levels for TP73L. TP73L was therefore not identified as a significant marker for GCTOB in their study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with a putative osteogenic origin of SC, osteoid foci may be found both inside and at the periphery of GCT [8,41], and bone formation, but no evidence of osteoclastogenesis has been observed in immunodeficient mice after subcutaneous injection of GCT tissue or cells [2,24]. Molecular profiling of GCT has recently demonstrated RANKL is highly expressed in GC but not in SC, suggesting the GC component of GCT is unlikely to be recruited as a result of RANKL production by SC [35]. Thus, neither cytogenetic nor molecular analysis has provided consistent evidence the SC are the neoplastic element.…”
Section: Introductionmentioning
confidence: 82%
“…As a result of the presence of a remarkably high number of osteoclast-like GC, early researchers suggested GCT was a neoplasm of the osteoclastic lineage, hence the term ''osteoclastoma'' [7]. However, GC show typical features of normal osteoclasts, including calcitonin and vitronectin receptor expression, tartrate-resistant acid phosphatase (TRACP) activity, and lacunar resorption ability [1,14,30,35]. SC were therefore believed the most likely candidate neoplastic elements of GCT, partly based on their ability to grow both in vitro and in vivo [2,24].…”
Section: Introductionmentioning
confidence: 99%